The Off-Targets of Clustered Regularly Interspaced Short Palindromic Repeats Gene Editing - Vicente, Manuel M.; Chaves-Ferreira, Miguel; Jorge, João M. P.; Proença, João T.; Barreto, Vasco M. (Frontiers in Cell and Developmental Biology, 2021)
The repurposing of the Cas/clustered regularly interspaced short palindromic repeat (CRISPR) bacterial defense system against bacteriophages as simple and flexible molecular tools has revolutionized the field of gene editing. These tools are now widely used in basic research and also in clinical trials involving human somatic cells. However, a global moratorium on all clinical uses of human germline editing has been proposed because the technology still lacks the required efficiency and safety. Here we focus on the approaches developed since 2013 to decrease the frequency of unwanted mutations (the off-targets) during CRISPR-based gene editing.